Daydreamer - Cameron, Rob (Labyrinth Road, 2024)
Split between two worlds, his real one, in which he's a lonely, bullied kid, and a magical realm called the Sanctuary, eleven-year-old Charles finds reality and imagination colliding when evil moves into his apartment building, and he must harness the power of his creativity to save both worlds.